HUBUNGAN FREKUENSI KUNJUNGAN POLIKLINIK KESEHATAN DESA (PKD) DENGAN SIKAP IBU TERHADAP PELAYANAN PKD DI WILAYAH KERJA PUSKESMAS BUAYAN 2010 - lestari, dinar binugraheni; -, marsito; novyriana, eka (Jurnal Ilmiah Kesehatan Keperawatan, 2010)
Mortality and morbidity is major problems in developing countries like Indonesia. Based on Indonesian demographic survey, the Maternal Mortality Rate (MMR) reaches 228/100.000 live births, Infant Mortality Rate (IMR) reaches 34/10.000 live births and MMR in Central Java province reaches 121/100.000 live births. IMR and MMR reduction target is expected to be succeed by establishing Making Pregnancy Safer (MPS) that initiated by the World Health Organization (WHO) and Health Departments of Indonesia. The Indonesian government issued Presidential Decree No. 32 in 1994 that states an appointment to midwives as temporary employees which will be utilized in rural areas which will occupy the village health clinic as the facilities and health service place in order to improve the quality and approach to maternal and child health including family planning as well as emergency cases to the community. The Objective of this study is to find out correlation between village polyclinic visit frequencies with mothers’ attitudes to polyclinic’s services in the Buayan Community Health Center work area. It is a descriptive analytical research that used cross sectional approach. There were 96 respondents taken as the samples by using cluster random sampling technique. The primary data were obtained through questionnaires. This study  Showed that there was a significant relationship between frequency of visits with mothers attitude towards the health services in the Buayan Community Health Center work area (p = 0.000 <0.005). The majority of respondents who did frequency visits in Buayan Community Health Center was classified in adequate category (56 respondents or 58.3%). Mother's attitude toward the health service in the working area in Buayan community health center was classified in is good less category (73 respondents or 76%).   Keywords: Visits Frequency, Maternal attitudes in Village polyclinic’s services